Lepidochelys olivacea status and its relationship with nest management on the eastern coast in the Pacifico of Guatemala - Morales Mérida, Berta Alejandra (2021)
Doctorado En Ciencias Naturales para el Desarrollo con énfasis en Gestión de los Recursos Naturales